ANALISIS PERSEPSI DAN PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN SAMPAH RUMAH TANGGA DI JAKARTA SELATAN - Aditya Nugraha; Surjono H. Sutjahjo; Akhmad Arif Amin (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Population growth and changes in consumption pattern have increased the municipal waste volume in DKI Jakarta. Waste management issue has been more formidable after the government has failed to overcome the situation with sufficient waste management facilities. Hence, society’s active participation is needed to create a more comprehensive system of municipal waste management, based on “reduce, reuse, recycle” principle. The objective of this study is to (1) identify the community perception and participation in the household waste management, (2) analyze the correlation between the internal and external factors of individual with the perception on the household waste management, and (3) analyze the correlation between community perception and participation in household waste management. The observed variables are divided into two factors, namely internal factors and external factors. The data were collected using survey method by distributing questionnaire, while Chi Square Test and Spearman Rank Correlation Test were used for data processing. The results showed that respondents have positive perception and high participation in the household waste management. There is a significant correlation between the internal and external factors of individual with community perception on the household waste management. Community perception on household waste management is also significantly correlated to community participation in household waste management.